PROFESSIONALISM OF CIVIL SERVANTS IN THE IMPLEMENTATION OF ADMINISTRATIVE LAW: A QUALITATIVE STUDY OF GOVERNMENT INSTITUTIONS IN INDONESIA - Ganta Pratama; Cholidah Utama (Multidisciplinary Research Studies in Social Sciences, 2026)
Professionalism in the civil service is essential to ensure justice, accountability, and ethical governance within Indonesia’s administrative system. This study examines how professionalism serves as a bridge between law and ethics in the implementation of administrative law. The main objective is to explore civil servants’ perceptions, practices, and institutional challenges in applying administrative law through professional conduct. Using a qualitative descriptive approach with a case study method, data were collected through in-depth interviews, document analysis, and direct observation in selected government institutions. The findings reveal four key themes: the perception of professionalism as moral and legal responsibility, institutional barriers such as bureaucratic hierarchy and weak supervision, ethical and legal integration, and improved governance outcomes marked by higher accountability and reduced maladministration. The results demonstrate that professionalism mediates ethical behavior and legal compliance, reinforcing transparency and justice in public administration. This study contributes to refining Good Governance Theory and provides practical insights for developing professional, ethical, and accountable bureaucratic systems in Indonesia.Keywords: administrative law, ethics, governance, professionalism, public administration